Simply Feng Shui - Bartlett, Sarah, 1952- (New York, NY : Sterling/Zambezi, 2010)
In this hectic world, we all need a moment to calm and re-center our minds and bodies. Meditation provides a natural way to do just that, and to open ourselves to the positive influences that surround us each day. This newest entry in the successful "Simply(R)" series takes beginners through the various steps of meditation, from choosing a location and focusing your mind to the various mediation methods, symbols, and psychic and religious connections. Many of the meditations are quick and easy, and some can even be done on the go. Beautiful illustrations and tip boxes throughout guide readers down the serene path as they de-stress and balance the flow of the mind.
Making a start -- The bagua -- The bagua sectors -- The five elements -- The best personal direction -- The environment -- Harmonizing Ch'i in the home -- More Ch'i in the home -- Elemental dates -- The five elemental personality types -- Creating a sacred corner -- Relationships -- Harmonizing love relationships -- Career, prosperity, and business -- Career choices -- Interiors and decorating -- Conclusion.
Includes index.
Keywords: Feng shui